2018
DOI: 10.1111/jzs.12218
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of a genital organ under sexual selection in Monacha kuznetsovi from the Caucasus (Gastropoda: Hygromiidae)

Abstract: During mating the dart apparatus of the land snail group Helicoidea transfers an allohormone that increases paternity success. Thus, this organ is under sexual selection. Despite this selective advantage, the dart sac has independently been lost in many lineages in the Helicoidea, presumably because natural selection counteracts sexual selection. However, the selective pressures that result in the loss of the organ have not been examined experimentally because most species show no variation in the presence or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Molecular analyses in the past 15 years have led to numerous systematic rearrangements in helicoid land snails (Wade et al, 2007; Hugall and Stanisic, 2011; Gómez‐Moliner et al, 2013; Razkin et al, 2015; Neiber et al, 2017; Sei et al, 2017). Moreover, it could be shown that reconfigurations, transformations and reductions of the dart apparatus have evolved many times in parallel in this superfamily (Hirano et al, 2014; Köhler and Criscione, 2015; Walther et al, 2016, 2018; Neiber and Hausdorf, 2017; Neiber et al, 2017, 2018a; Chueca et al, 2018), and it may even differ considerably among closely related taxa or within a single species (Korábek et al, 2015; Neiber and Hausdorf, 2015; Kruckenhauser et al, 2017; Zopp et al, 2017; Neiber et al, 2018b). In Geomitrini, the calcareous dart has been lost and the dart sac or the accessory sac has been transformed to a hollow tube, the appendicula.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular analyses in the past 15 years have led to numerous systematic rearrangements in helicoid land snails (Wade et al, 2007; Hugall and Stanisic, 2011; Gómez‐Moliner et al, 2013; Razkin et al, 2015; Neiber et al, 2017; Sei et al, 2017). Moreover, it could be shown that reconfigurations, transformations and reductions of the dart apparatus have evolved many times in parallel in this superfamily (Hirano et al, 2014; Köhler and Criscione, 2015; Walther et al, 2016, 2018; Neiber and Hausdorf, 2017; Neiber et al, 2017, 2018a; Chueca et al, 2018), and it may even differ considerably among closely related taxa or within a single species (Korábek et al, 2015; Neiber and Hausdorf, 2015; Kruckenhauser et al, 2017; Zopp et al, 2017; Neiber et al, 2018b). In Geomitrini, the calcareous dart has been lost and the dart sac or the accessory sac has been transformed to a hollow tube, the appendicula.…”
Section: Introductionmentioning
confidence: 99%